Industry-specific firm growth and aggolmeration - Matthias Duschl; Tobias Scholl; Thomas Brenner; Dennis Luxen; Falk Raschke (Philipps-University Marburg, Department of Geography, 2012)
This paper studies the industry-specific relationship between industrial clustering and firm growth. Micro-geographically defined agglomeration measures, free of the modifiable areal unit problem (MAUP), are used to study 23 industries. The spatial impacts of agglomeration of related economic and knowledge generating activities are examined by using travel time distances, a flexible log-logistic decay function framework and quantile regression techniques. We find that firms' growth prospects tend to be hampered by the agglomeration of own-industry employment, but improved by proximate scientific activity. Results depend on the kind and age of industry. Furthermore, the optimal decay functions that measure agglomeration effects considerably vary both between the industries and variables. Three illustrative cases of industries are discussed in more details.
Keywords: C31; D92; L25; R11; 330; Firm growth; industrial clusters; agglomeration; MAUP; distance decay function; quantile regression